Clinical Outcome of Wedge Resection Procedure for Ingrown Toe Nail - Mudassar Nazar, M. Waseem Anwar, M. Arif, M. M. Yasin Awan, G.R. Nawaz Khan, M. Arshad Abbas, Hassan Raza Khosa (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the results of the wedge resection procedure in the treatment of ingrown toenails Place and duration of study: The detailed study was carried out at Shahida Islam Medical College Lodhran and Rajib Tayyip Erdogan Hospital, Muzaffargarh, between September 2020 to August 2022. Methods: We conducted a prospective study on 73 patients who underwent wedge resection procedures between Sept 2019 to August 2021. We noted the demographic details like mean age, gender distribution, postoperative complication rate, recurrence rate, and satisfaction with the procedure. Results: The mean age(SD) was 29.3 (4.7) years with 33% males and 67% females. Wefound that 6 min was the average duration of the procedure and only two patients had postoperativecomplications; 99% were satisfied with the outcome and only 1.37% showed recurrence of the issue. Conclusion: We can conclude Wedge Resection Procedure is a safe, effective, and convenient technique in the management of ingrown toe nails. Keywords: ingrown toenail, Wedge Resection Procedure (WRP)